2015
DOI: 10.1002/job.2054
|View full text |Cite
|
Sign up to set email alerts
|

When are overqualified employees creative? It depends on contextual factors

Abstract: Summary The research on perceived overqualification has mainly examined its negative consequences. Defined, employees who feel overqualified have surplus talent and thus can be excellent workers if managed properly; yet, empirical evidence in this domain is lacking. Building on person–environment fit theory, this research explored whether, when, and how employees who feel overqualified can engage in creative performance. The results of a multi‐source field study (N = 113 employees and 19 supervisors) supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(190 citation statements)
references
References 92 publications
(196 reference statements)
8
177
1
4
Order By: Relevance
“…First, our study counterproductive work behaviors (Liu et al, 2015, or creativity (Luksyte and Spitzmueller 2015). Further, consistent with a finding that job autonomy helps mitigate the negative consequences of perceived overqualification on job satisfaction especially in highly individualistic countries (Wu et al, 2014), our findings in Study 2 suggest usefulness of granting higher job autonomy in mitigating the negative consequences of perceived overqualification on employees' adaptive behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…First, our study counterproductive work behaviors (Liu et al, 2015, or creativity (Luksyte and Spitzmueller 2015). Further, consistent with a finding that job autonomy helps mitigate the negative consequences of perceived overqualification on job satisfaction especially in highly individualistic countries (Wu et al, 2014), our findings in Study 2 suggest usefulness of granting higher job autonomy in mitigating the negative consequences of perceived overqualification on employees' adaptive behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 77%
“…Practically, given the current findings, our results suggested that organizations concerned about losing overqualified employees, who can be adaptive or creative (Luksyte and Spitzmueller 2015) if the conditions are right, first have to identify those who feel overqualified, and then implement effective strategies to encourage their adaptive behaviors.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Therefore evaluation and findings related to the subject were completed by way of literature review. As indicated by Luksyte and Spitzmueller (2016) although important information was provided from the research related to the negative consequences of overqualification, it is crucial to place the inadequately researched positive consequences of overqualification in future studies from now onward.…”
Section: Resultsmentioning
confidence: 99%
“…Need-supplies fit has mediated better the relation between employees perceived overqualification relation with interpersonal influences and helping behavior and demand fit supply has explained the work deviance relation with employees perceived over-qualification, conversely, the necessities of employees who sense overqualified are not sufficiently satisfied, resulting in higher workplace deviance behavior. Aleksandra Luksyte and Spitzmueller (2016) have examined the positive aspect of perceived overqualification under personenvironmental fit theory and concluded that result supported the theory and perceived overqualification is positively related to supervisor creative performance due to which worker felt supportive. Consistent with PE fit theory and covering it more, we concluded that for employees who feel themselve as overqualified, improving both types of fit have improved and motivate their interpersonal influence and helping behavior and decrease their deviance behavior.…”
Section: Introductionmentioning
confidence: 90%